G32 Variation in upper GI bleeding service provision for children in the United Kingdom – a nation-wide survey by British Society of Paediatric Gastroenterology Hepatology and Nutrition (BSPGHAN). (27th April 2016) - Afzal, NA; Lloyd, C; Narula, P; Gupte, G; Croft, NM; Baker, A
Abstract : Aims: The CROMES Report (2007) shows significant variability in provision of acute upper GI bleeding services for adult in the UK. With no information available regarding paediatric upper gastrointestinal bleeding services (pUGIBS), BSPGHAN conducted a nationwide survey; the aim to assess the provision of pUGIBS in the United Kingdom. Methods: The national survey was conducted, designed and led by the BSPGHAN executive. The questions were finalised after 'face validation' and are in a yes/no and multiple choice question formats with free text space for comments. The questions were direct, relating to provision of services, 24/7 cover, availability of written protocols and presence of local lead. The survey was conducted online and one reply per centre chosen to be representative of services in the hospital. Results: 25 BSPGHAN members from 15 units in the United Kingdom (England, Wales, Scotland, N. Ireland) participated in the survey. Paediatricians in Paediatric liver (pLiver), paediatric Gastrointestinal (pGI) and paediatric services in district general hospitals (pDGH) participated in the survey. 8/10 of the pGI units offered upper paediatric GI bleeding services with a 24/7 out of hours provision offered only by 5/10 units (2/7 pGI and 3/3 pGI+pLiver centres). 6/10 pGI centres had a designated pUGIBS clinical lead with 5/9 of these pGI centres with a protocol for banding for management of bleeding varices. Only 6/15 units of all paediatric centres had an acute upper GI bleeding management protocol. Conclusions: Despite limited representation, the survey reflects a country wide variation in paediatric upper gastrointestinal bleeding service, similar to adult services as in the CROMES report. Additionally, paucity of acute upper GI bleeding management protocols highlight the urgent need for developing local and national guidance with standards. The paediatric endoscopy working group (BSPGHAN) is assisting JAG (Joint advisory group on GI endoscopy) to develop a new paediatric endoscopy service assessment tool. This will help to conduct regular annual audits, benchmarking against other paediatric endoscopy units therefore helping to implement quality standards in pGI units in the UK.